"If Only My Coworker Was More Ethical": When Ethical and Performance Comparisons Lead to Negative Emotions, Social Undermining, and Ostracism - Quade, Matthew J.; Greenbaum, Rebecca L.; Mawritz, Mary B. (Journal of business ethics, 2019)
Drawing on social comparison theory, we investigate employees' ethical and performance comparisons relative to a similar coworker and subsequent emotional and behavioral responses. We test our theoretically driven hypotheses across two studies. Study 1, a cross-sectional field study (N=310 employee–coworker dyads), reveals that employees who perceive they are more ethical than their coworkers (i.e., more ethical comparison) experience negative emotions toward the comparison coworkers and those feelings are even stronger when the employees perceive they are lower performers than their coworkers (i.e., lower-performance comparison). Results also reveal that negative emotions mediate the indirect relationship between being more ethical than a coworker, but also being a lower performer than that coworker onto (a) social undermining and (b) ostracism. Study 2, a 2×2 between-subjects experimental design (N=121), provides further support for our moderated mediation model. Results reveal that participants experience negative emotions when they receive information that they are more ethical than a comparison participant. Negative emotions are amplified if the participant is told they were a lower performer than the comparison participant. Those participants indicate their desire to mistreat and ignore the comparison participant if given the opportunity. Thus, we find support for our hypotheses using a multi-method design.